Study of plasma cutting efficiency with different operating parameters - Masita binti Raja Mohammad (School of Manufacturing Engineering, Universiti Malaysia Perlis, 2010)
Plasma, a fourth state of matter distinct from solid or liquid or gas and present in stars and fusion reactors; a gas becomes plasma when it is heated until atoms lose all their electrons, leaving a highly electrified collection of nuclei and free electrons. The usage of advanced machining, such as Plasma Arc Cutting machine to cut Mild Steel, Copper Alloy and Aluminium was very limited in the industry. Selco Genesis 90 Plasma Arc Cutting machine was used to cut Copper Alloy, Aluminium and Mild Steel in this study. The usage of Taguchi approach Design of Experiments from the designing steps until the analyzing phase from the experiment was used. In this study, Design of Experiment L-9 (34) layout is used. In this study, the parameters determined were the air pressure [bar], current flow rate [A], cutting speed [mm/min] and arc gap [mm]. These parameters used to analyze the setting required for optimizing the process variables for Plasma Arc Cutting machine to gain the best combination. The effect of these factors was the calculation of Material Removal Rate (MRR) and Surface Roughness (Ra). Confirmation test must be done to confirm the value estimated through the software. The confirmation run was done by using the setting gain from the software. The estimated optimum value and the actual value obtained from the confirmation test that is allowed are in range 10%.